2013
DOI: 10.1088/0022-3727/46/41/415304
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nanoparticles by means of reflection electron energy loss spectroscopy depth profiling

Abstract: The various studies of nanoparticles are of great importance because of the wide application of nanotechnology. The shape and structure of the nanoparticles can be determined by transmission electron microscopy (TEM) while their chemistry by electron energy loss spectroscopy (EELS).TEM sample preparation is an expensive and difficult procedure, however. Surface sensitive, analytical techniques, like Auger electron spectroscopy (AES), X-ray photoelectron spectroscopy (XPS) are well applicable to detect the atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The 2 nd C, 2 nd Si and 3 rd C layers are unaffected by the irradiation, which is expected since the penetration (projected range) of 30 keV Ga in this layer system is 24±7 nm. We have shown that the measure of intermixing increased with fluence [15] and that majority of SiC was amorphous nano particles [18]. The intermixed layer besides SiC always contained Ga and if the fluence was ≤ 20 x 10 15 Ga + /cm 2 free (non-reacted) C and Si as well.…”
Section: The Initial Conditionmentioning
confidence: 86%
See 2 more Smart Citations
“…The 2 nd C, 2 nd Si and 3 rd C layers are unaffected by the irradiation, which is expected since the penetration (projected range) of 30 keV Ga in this layer system is 24±7 nm. We have shown that the measure of intermixing increased with fluence [15] and that majority of SiC was amorphous nano particles [18]. The intermixed layer besides SiC always contained Ga and if the fluence was ≤ 20 x 10 15 Ga + /cm 2 free (non-reacted) C and Si as well.…”
Section: The Initial Conditionmentioning
confidence: 86%
“…These plasmon losses can be utilized for the identification of the particles. Reflection electron energy loss spectroscopy (REELS) was used to identify the appearance of SiC and Ga particles [18].…”
Section: Detection Of Particle Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…These regions will not be considered from the point of view of IBM induced SiC production. Low energy (1 keV) REELS measurements exhibited the bulk plasmon loss of SiC, showing that considerable amount of SiC is located in nanoparticles with sizes of larger than 1-2 nm [19]. 120 keV Xe + irradiation to a fluence of 1 × 10 16 Xe + cm −2 (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…C and Si was visualized by EELS elemental mapping. Reflection electron energy loss spectroscopy (REELS) measurement at low, 1 keV, primary electron energy was used to measure the plasmon energy of the nano-particles produced [19] giving a limit of the particle size.…”
Section: Ion Beam Mixingmentioning
confidence: 99%